Nursing Staff Develop a Video to Prevent Falls: A Quality Improvement Project. Issue 1 (January 2016) - Silkworth, Amelia L.; Baker, Jennifer; Ferrara, Joseph; Wagner, Molly; Gevaart, Melinda; Morin, Karen
Abstract : Many fall prevention strategies exist with some degree of effectiveness. Evidence to support 1 unique bundling of strategies is limited. The purpose of this article is to describe a staff-driven quality improvement initiative to develop a video in partnership with patients and families to prevent falls when hospitalized. Since the video's release, the fall rate has decreased by 29.4%. Abstract : Supplemental Digital Content is Available in the Text.